Nobodaddy's Kinder - Schmidt, Arno (Suhrkamp, 2005)
Three novellas on Germany from the Nazi era through the postwar years. In Aus dem Leben eines Fauns , a civil servant tries to forget the war by researching the exploits of a deserter during the Napoleonic Wars; Brand's Haide is about a returning prisoner-of-war; and in Schwarze Spiegel, the lone survivor of atomic warfare discovers he is not alone.
9783518417102
Keywords: Historical fiction; Geschichte; Nuclear warfare; Veterans